Level of Education Provided by Nurses to the Parents of Children with Chemotherapy-Induced Mucositis - Mohammad Arshadi Bostanabad; Tahereh Alvandnezhad; Amirataollah Hiradfar; Asghar Mohammadpoorasl; Bagher Khalvati (Golestan University Of Medical Sciences, 2018)
Introduction: Mucositis is a side effect of chemotherapy, which affects patients' quality of life. Nurses are the main care providers for cancer patients. Choosing a suitable care strategy is a challenge faced by oncology nurses. Educating patients about management of cancer therapy complications results in optimal use of healthcare services and improves quality of life of patients. The aim of this study was to evaluate level of health education provided by nurses to the parents of children with chemotherapy-induced mucositis. Materials and methods: This descriptive study was conducted in 2016 on 60 children (mean age 86.7 ± 39.16 months) with chemotherapy-induced mucositis at the Children's Hospital of Tabriz, Iran. Demographic information and health education offered in conjunction with the mucositis clinical records were obtained through interviews with the parents. The data were analyzed in SPSS 12, using chi-square test and t-test. Results: Only 3.3% of the subjects received appropriate training in relation to mucositis, whereas 56.6% received no training and 40% received partial training. Conclusions: Our results suggest that the level of training provided for children with chemotherapy-induced mucositis is not satisfactory. Therefore, nursing authorities and planners should prepare the nursing personnel to provide care and special support to these patients.